Evaluation of the correlation between perfusion index and prognosis in patients with chronic obstructive pulmonary disease - Demir, Mehmet; Cander, Basar; Ayvacı, Barış Murat (The European Research Journal, 2022)
Objectives: This study aims to investigate whether perfusion index (PI) values, which are measured non-invasively, affect emergency management, especially in hospitalization and discharge decision in patients with Chronic Obstructive Pulmonary Disease (COPD). Methods: Patients who were admitted to the emergency department of Okmeydanı Training and Research Hospital with a COPD exacerbation in 3-months period and who volunteered to participate were included in the study. Vital parameters and PI values of the patients at the time of admission, at the first, second and third hour of the admittance and at the time of hospitalization (in the case of hospitalization) were recorded. The patients were treated for COPD exacerbation according to the Global Initiative for Chronic Obstructive Lung Disease 2011 guide and the decision of discharge, hospitalization in the emergency department, andhospitalization in the intensive care unit was taken based on the relevant guideline. Results: A total of 57 patients were included in the study. Of the patients, 45 (78.9%) were male. The mean age of the patients was 65.65 ± 9.90 years. There was no statistically significant difference in arrival vital parameters and PI in terms of the gender (p > 0.05). The change between PI values at the time of admission and the first hour in the patients admitted to intensive care unit was found to be significantly lower compared to patients who were hospitalized in the emergency department or discharged (p = 0.035; p = 0.033). The difference between the PI values at the time of admission and at the third hour of the follow up of the discharged patients was found to be significantly higher compared to the hospitalized patients (p = 0.035). There was no statistically significant difference between the arrival PI measurements in terms of the presence of comorbid diseases (p > 0.05). Conclusions: Considering the hourly changes, the PI values of patients admitted to the emergency department with COPD exacerbation may be helpful in predicting the decision of discharge, hospitalization in the emergency department or intensive care unit.